International Marketing / Second Edition - Paliwoda Stanley (Butterworth Heinemann, 1993)
The ideal marketing book for the 1990s. International Marketing in a Global Economy, Identifying International Marketing Opportunities, Exporting and the Small Business, Monitoring the Effectiveness of Market Entry Strategies, Product Policy Decisions, Logistics and Marketing Channel Decisions, International Marketing Planning, International Marketing Control Systems, Marketing to Japan, Marketing to the Single European Market, Marketing in China, Case Studies, Index.